2021
DOI: 10.1002/oby.23108
|View full text |Cite
|
Sign up to set email alerts
|

Obesity‐Associated Myeloid Immunosuppressive Cells, Key Players in Cancer Risk and Response to Immunotherapy

Abstract: Obesity is a risk factor for developing several cancers. The dysfunctional metabolism and chronic activation of inflammatory pathways in obesity create a milieu that supports tumor initiation, progression, and metastasis. Obesity-associated metabolic, endocrine, and inflammatory mediators, besides interacting with cells leading to a malignant transformation, also modify the intrinsic metabolic and functional characteristics of immune myeloid cells. Here, the evidence supporting the hypothesis that obesity meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…This possibility is important considering that additional signals could derive from infectious agents or malignant cells. It is known that excess weight increases the risk of developing severe infections 18 , 42 and cancer, 43 , 44 suggesting a potential contribution of LDN in developing or exacerbating these co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is important considering that additional signals could derive from infectious agents or malignant cells. It is known that excess weight increases the risk of developing severe infections 18 , 42 and cancer, 43 , 44 suggesting a potential contribution of LDN in developing or exacerbating these co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms include reduced absolute numbers of activated CD8 + T cells, T cell suppression by PD-1 [241,242], T cell exhaustion [243], and dysfunctional NK cells [244]. Thus, obesity induces a complex and dynamic state of pro-inflammatory immune cell content and function with an influx of monocyte-derived "M1"-like macrophages, combined with reductions in immunomodulatory/ regulatory or dysfunctional immune cells such as regulatory T cells (Tregs), "M2"-like macrophages, or NK Cells, together with an induction of checkpoint ligands (discussed below) [245][246][247][248], and elevated immunosuppressive cells such as immature monocytes or myeloid-derived suppressive cells (MDSCs) [249][250][251][252][253]. Peripheral Treg levels are reduced in correlation with increasing adiposity in humans [254,255].…”
Section: Bariatric Surgery and The Immune Systemmentioning
confidence: 99%
“…Traditional methods for quantifying tumor immune cells infiltration based on histology or immunohistochemistry may have bias and variabilities (Yoshihara et al, 2013;Gibney et al, 2016;Spranger and Gajewski, 2018;Zhang et al, 2020;Sanchez-Pino et al, 2021). More recently, RNA-seq analyses have shown that lncRNAs exhibit a better degree of cell type specificity, relative to protein-coding genes in immune cells, highlighting their potential as subpopulation-specific immune cells molecular markers (Huang et al, 2018;Chen et al, 2019;Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines and chemokines production by invasive neutrophils might affect the recruitment and activation of inflammatory cells in the TME, create an immunosuppressive microenvironment that is conducive for tumorigenesis, regulate tumor growth, metastasis and angiogenesis, and influence patient prognosis. Traditional methods for quantifying tumor immune cells infiltration based on histology or immunohistochemistry may have bias and variabilities ( Yoshihara et al, 2013 ; Gibney et al, 2016 ; Spranger and Gajewski, 2018 ; Zhang et al, 2020 ; Sanchez-Pino et al, 2021 ). More recently, RNA-seq analyses have shown that lncRNAs exhibit a better degree of cell type specificity, relative to protein-coding genes in immune cells, highlighting their potential as subpopulation-specific immune cells molecular markers ( Huang et al, 2018 ; Chen et al, 2019 ; Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%